SIMULTÂNEA DE METAIS EM BIODIESEL, POR VOLTAMETRIA DE REDISSOLUÇÃO ANÓDICA USANDO ELETRODO DE FILME DE MERCÚRIO EM MEIO ALCÓOLICO - Frazão, érica Vanessa Pereira (2010)
Diferential pulse and square wave anodic stripping voltammetry at the mercury film electrode, prepared in the ex-situ and in-situ modes, showed an adequate analytical performance and were employed for the development of a procedure for analysis of Biodiesel. Samples were simply diluted into a methanol solution to a final concentration of 0.33 mol L-1 (v/v) acetic acid in order to convert the analytes to their inorganic form. Supporting electrolyte was evaluated among several (1x10-2 mol L-1 LiCl, 5x10-2 mol L-1 H2SO4 in ethanol media and CH3COONa 1x10-2 mol L-1 and CH3COOH 2% in methanol media). 2% (3.3x10-1 mol L-1) acetic acid in methanol media was chosen, and the pH adjusted to a final value of 4.5 with NaOH (2.0 mol L- 1) due to its ability to provide adequate solubility for biodiesel. After several voltammetric experiments in the absence and presence of increasing aliquots of pure biodiesel and metal standard solution, the ideal set of voltammetric procedure for the simultaneous determination of metals was obtained as following: Edep: -1.0 V; Efinal: 0.1 V; tdep: 160 s, amplitude: 75 mV, frequency: 20 Hz. Voltammograms and their corresponding standard curves indicated that the procedure for simultaneous determination is viable. The results obtained indicated that anodic stripping voltammetry in the square-wave mode (SVSW) shown extremely useful and more sensitive results than pulse diferential mode for simultaneous measurements of metal trace in B100 at nanomolar level. On the other hand linear sweep stripping voltammetry did not presented sensitivity enough in the studied conditions. The experiments carried out by adding successive aliquots of a standard mixed solution of Pb, Cu and Cd (1x10-5 mol L-1), provided a linear response between current and concentration of metals (correlation coefficient for lead and copper were respectively 0.996 and 0.997 (EFM prepared ex-situ) and 0.996, 0.990 and 0.990 (EFM prepared insitu) for lead, copper and cadmium metals). Each sample of biodiesel was analyzed in triplicate. In-situ and ex-situ mercury film electrodes were evaluated showing both appropriate analytical performance. The procedures showed very good results of statistical evaluation for a 95% of confidence level.